STRATEGI BRANDING PANTI SOSIAL (STUDI DESKRIPTIF KUALITATIF MENGENAI STRATEGI BRANDING UNIT INFORMASI DAN LAYANAN SOSIAL MERUYA) - Dwi Ramayanti; Annisa Rachimi Rizka (Universitas Mercu Buana, 2020)
Unit Infomasi dan Layanan Sosial (UILS) is a place for those of us who experience mental/mental disabilities to gather, share, and carry out various activities in a comfortable and friendly atmosphere. The lack of fostered residents at UILS Meruya indicates that the Social Services Unit cannot play a leading role while having a big vision of the eradication of psychotic problems in DKI Jakarta Province in a decent, normative and humane life. Branding strategy is needed to increase public awareness of a brand. This research was conducted to determine the branding strategy owned by UILS Meruya. The research method used in this study was a qualitative descriptive method. Qualitative descriptive method is a research procedure based on descriptive data, using analysis. The theoretical basis as a reference so that the focus of research by the facts in the field. The approach taken is by interview, observation, and literature study. Researchers, together with UILS Meruya stakeholders, have analyzed and formulated brand positioning, brand identity, and brand personality from UILS Meruya.